2022
DOI: 10.30574/wjarr.2022.15.2.0793
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori (H. pylori) by histochemical stains in gastric biopsy comparing to immunohistochemistry

Abstract: Aim: A reliable diagnosis of Helicobacter pylori (H. pylori) is important in clinical practice and research. The aim of this study was to compare the sensitivity and specificity of Giemsa stain with hematoxylin and eosin (H&E), Toluidine blue, Gimenez and Warthin-Starry stain in detection of Helicobacter pylori (H. pylori) in gastric biopsy and also with immunohistochemistry (IHC) stain in detection of H. pylori organism in gastric biopsy. Method: A retrospective cross-sectional included 200 formalin-fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The level of statistical significance was set at P < 0.05. Sensitivity and specificity were calculated based on the following formulae: Sensitivity= (True positive/(True positive + False negative)) * 100%; Specificity= (True negative/(True negative + False positive)) * 100% ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…The level of statistical significance was set at P < 0.05. Sensitivity and specificity were calculated based on the following formulae: Sensitivity= (True positive/(True positive + False negative)) * 100%; Specificity= (True negative/(True negative + False positive)) * 100% ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the study done by Kocsmár et al, Giemsa revealed an overall sensitivity of 83.3% and a specificity of 98.8%. 20 , 21 Also, PCR can be used for detection of H. pylori using samples from gastric juice, gastric biopsy, dental plaque, saliva, and stools. Moreover, it was reportedly used to find H. pylori in middle ear effusion collected.…”
Section: Introductionmentioning
confidence: 99%